Food safety: perspective and challenges - Rahmat Ali, Gulam Rusul (2002)
Food Safety is major concern for consumers, food producers, processor and regulatory agencies. It is concerned with ensuring food that is safe or free from disease causing agents such as microorganisms, biological toxins and chemicals form the FARM TO THE TABLE, or throughout the FOOD CHAIN. In the last decade, incidents of food related disease outbreaks, such as Bovine Spongiform Encephalopathy (BSE), Foot and Mouth Disease (FMD, Febrile Encephalitis (Nipah Virus), Dioxin contamination of animal feeds, Staphylococcus aureus entertoxin in snow-brand milk powder and Influenza virus in poultry (Hong Kong),have caused significant economic losses and attracted a lot of media attention. These outbreaks lead to human illness, deaths, destruction of livestock, closure of farms and processing plants resulting in losses amounting to billion of dollars.